Religious and Political Factor in Iran's Foreign Policy in Central Asia (International relations and international law Journal, 2023)
This article highlights the role of the religious factor in Iran's foreign policy in Central Asia. In order to determine the priority directions of the foreign policy of the Islamic Republic of Iran, the stages of formation and development of foreign policy towards Central Asia were analyzed. The significance of the concept of "Shiа crescent" (Shiа triangle) has been studied as the main direction of Iran's foreign policy and its reflection in cooperation with the countries of Central Asia and the Middle East. In the foreign policy of official Tehran in relation to the countries of the region, the reasons for rejecting the idea of "exporting" the revolution and the reasons for reorientation to a pragmatic policy were also analyzed. Iran's approaches to solving security problems in Central Asia have been studied. Special attention was paid to the strategic importance of Iran for Central Asia, at the present stage, common interests and directions for the development of economic relations between Iran and the Central Asian states were highlighted. In the 90s of the last century, Iran, using religious rhetoric, tried to lay the foundation for a policy towards the countries of Central Asia. It can be said that the countries of the region found themselves in such a difficult situation as the choice between a secular regime and a religious renaissance. Despite the confessional differences with the countries of the region, it should be noted that Iran sought to support political Islamic groups in the region.Key words: Iran, Shiism, Central Asia, religious factor, exporting the revolution, Islam.